We celebrate Hallowe'en - Kalman, Bobbie, 1947-; Drew-Brook-Cormack, Allan; Drew-Brook-Cormack, Deborah (Toronto ; New York : Crabtree Pub. Co., 1985)
Describes the origins of Halloween celebrations and traditions and how they differ throughout the world. Includes crafts, games, recipes, poems, and customs from various countries
Includes index
Keywords: Halloween -- Juvenile literature; Halloween